2015
DOI: 10.1186/s12913-015-1028-4
|View full text |Cite
|
Sign up to set email alerts
|

Should Governments engage health insurance intermediaries? A comparison of benefits with and without insurance intermediary in a large tax funded community health insurance scheme in the Indian state of Andhra Pradesh

Abstract: BackgroundA peculiar phenomenon of engaging insurance intermediaries for government funded health insurance schemes for the poor, not usually found globally, is gaining ground in India. Rajiv Aarogyasri Scheme launched in the Indian state of Andhra Pradesh, is first largest tax funded community health insurance scheme in the country covering more than 20 million poor families. Aarogyasri Health Care Trust (trust), the scheme administrator, transfers funds to hospitals through two routes one, directly and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…There was saving of some administrative cost under ‘Trust’ because no insurance firm was contracted to act as an intermediary. The study did not examine impact on OOPE but reported problem of formation of cartels by private hospitals [77]. We note that in the three states whose analysis was presented here, the experience is that PFHI schemes were unable to provide effective financial protection despite one opting for an Insurance model and two going for a Trust model and all three having a provider-purchaser split in place.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was saving of some administrative cost under ‘Trust’ because no insurance firm was contracted to act as an intermediary. The study did not examine impact on OOPE but reported problem of formation of cartels by private hospitals [77]. We note that in the three states whose analysis was presented here, the experience is that PFHI schemes were unable to provide effective financial protection despite one opting for an Insurance model and two going for a Trust model and all three having a provider-purchaser split in place.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the ‘Insurance’ intermediary model seems to involve relatively greater separation of policy making, purchasing and providing roles, compared to the ‘Trust’ model. In India, there is a current debate regarding design of purchasing arrangements under PFHIs - whether to use a Trust or Insurance Company as purchaser [12, 77]. A study of Andhra Pradesh has suggested that Trust model offered some advantages, especially in reducing administrative costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact on financial protection as measured through out-of-pocket expenditure and catastrophic headcounts was not significant [6][7][8][9][10]. Studies exploring the institutional and governance arrangements of these schemes indicate challenges that may have limited the achievement of scheme objectives [11][12][13][14]. Several of these challenges relate to the institutional arrangements for healthcare purchasing adopted in these schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on earlier schemes have indicated that when insurance company profits are linked to claim payouts, there are incentives to unnecessarily reject claims or empanel a limited number of hospitals, or hospitals with insufficient capacities to provide services [12][13][14]. Such misalignments of incentives between insurance companies and the government, suggest that healthcare purchasing through an insurance company may limit the achievement of programme objectives that seek to expand access.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affect enrollment include education status, lack of trust in health service providers, unclear regulatory framework for the CBHIs, enrollment requirements, managerial capacity, and previous health utilization history of households. CBHIs require substantial investment to start, and can be misunderstood by the informal sector (mainly the uneducated population), but may also lack political commitment ( 24 31 ).…”
Section: Introductionmentioning
confidence: 99%